Comparative evaluation of the effect of audio and virtual reality distraction on the dental anxiety of healthy and mild intellectually disabled children - Deepshikha Mehrotra; R Manju (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2023)
Context: Dental environment is one of the most anxiety-provoking stimuli for children, which makes patient management a constant challenge in both typically growing and intellectually disabled children. Distraction is a nonpharmacological technique to manage anxiety in children during dental treatment. Aim: This study compares the effect of audio and virtual reality (VR) distraction on the dental anxiety of healthy and mild intellectually disabled children. Methods: Forty children aged 6–14 years were divided into two groups (Group I: children with mild intellectual disability and Group II: healthy children). Groups I and II were further subdivided into two subgroups of 10 children each, based on the distraction technique given to them during the first appointment. After 1 month, we carried out a cross-over of the subgroups. Anxiety levels were measured using physiological and observational parameters at three-time intervals. Statistical Analysis: Performed using paired t-test for the intergroup comparison and Wilcoxon Signed Rank test for the intra-group comparison. Results: A decrease in the pulse rate, improvement in oxygen saturation levels, and lower Venham's anxiety rating scores were observed on introducing audio and VR distraction in all the subgroups. The inter-group comparison revealed that audio and VR were more effective in healthy children than children with mild intellectual disabilities. Conclusions: Audio and VR distraction techniques can be employed successfully to reduce anxiety in children with mild intellectual disability and healthy children undergoing dental restorative treatment.